A 6‐month randomized, double‐blind, placebo‐controlled trial of weekly exenatide in adolescents with obesity. Issue 7 (16th February 2020) - Weghuber, D.; Forslund, A.; Ahlström, H.; Alderborn, A.; Bergström, K.; Brunner, S.; Cadamuro, J.; Ciba, I.; Dahlbom, M.; Heu, V.; Hofmann, J.; Kristinsson, H.; et al.
Summary: Background: Pharmacological treatment options for adolescents with obesity are very limited. Glucagon‐like‐peptide‐1 (GLP‐1) receptor agonist could be a treatment option for adolescent obesity. Objective: To investigate the effect of exenatide extended release on body mass index (BMI)‐SDS as primary outcome, and glucose metabolism, cardiometabolic risk factors, liver steatosis, and other BMI metrics as secondary outcomes, and its safety and tolerability in adolescents with obesity. Methods: Six‐month, randomized, double‐blinded, parallel, placebo‐controlled clinical trial in patients (n = 44, 10‐18 years, females n = 22) with BMI‐SDS > 2.0 or age‐adapted‐BMI > 30 kg/m 2 according to WHO were included. Patients received lifestyle intervention and were randomized to exenatide extended release 2 mg (n = 22) or placebo (n = 22) subcutaneous injections given once weekly. Oral glucose tolerance tests (OGTT) were conducted at the beginning and end of the intervention. Results: Exenatide reduced ( P  < .05) BMI‐SDS (−0.09; −0.18, 0.00), % BMI 95th percentile (−2.9%; −5.4, −0.3), weight (−3 kg; −5.8, −0.1), waist circumference (−3.2 cm; −5.8, −0.7), subcutaneous adipose tissue (−552 cm 3 ; −989, −114), 2‐hour‐glucose during OGTT (−15.3 mg/dL; −27.5, −3.1), total cholesterol (11.6 mg/dL; −21.7, −1.5), and BMI (−0.83 kg/m 2 ; −1.68, 0.01) without significant change in liver fat content (−1.36; −3.12, 0.4; P = .06) in comparison to placebo. Safety and tolerability profiles were comparable to placebo with the exception of mild adverse events being more frequent in exenatide‐treated patients. Conclusions: Treatment of adolescents with severe obesity with extended‐release exenatide is generally well tolerated and leads to a modest reduction in BMI metrics and improvement in glucose tolerance and cholesterol. The study indicates that the treatment provides additional beneficial effects beyond BMI reduction for the patient group.